Tiazofurin-induced DNA damage in human whole blood cells detected by the in vitro comet assay - Topalović, Dijana; Živković, Lada; Đelić, Ninoslav; Bajić, Vladan; Spremo-Potparević, Biljana (Medicinski časopis, 2021)
Objective. Inosine 5’-monophosphate dehydrogenase (IMPDH) activity is increased in cancer cells. Tiazofurin selectively inhibits the activity of IMPDH, and it has been granted for the treatment of different cancers and new viral diseases. Its widespread use was limited because exposure to Tiazofurin under certain circumstances was found to have a higher incidence of serious non-hematologic toxicity. Therefore, the objective of this study was to examine genotoxic action and inducement of DNA damage of Tiazofurin using the comet assay. Methods. The ability of Tiazofurin to induce DNA damage was evaluated using single-cell gel electrophoresis (SCGE) technique/comet assay. Human whole blood cells were exposed to three final concentrations of Tiazofurin (1 µM/mL, 2 µM/mL, and 5 µM/mL) for 30 min in vitro. Results. Our results indicate that Tiazofurin produced a significant level of DNA damage on whole blood cells after 30 min of exposure vs. control. All tested concentrations were significantly comet-forming, in a concentration-dependent manner. Conclusion. Our investigation on the Tiazofurin-treated cells and their relationship to the formation of DNA damage demonstrated that the genotoxic effect was induced after exposure to Tiazofurin under described conditions.